A CASE OF NEONATAL SPINAL MUSCULAR ATROPHY WITH SEPSIS LIKE PRESENTATION - Yilmaz Gondal, Oznur; Yalin Imamoglu, Ebru; Yuksel Karatoprak, Elif (MNJ (Malang Neurology Journal), 2021)
Introduction: Spinal Muscular Atrophy (SMA) is a progressive neuromuscular disease causing degeneration of nerves at anterior horn of spinal cord. The most common and severe form is SMA type 1 which starts before 6 months of age. Patients do not survive more than 2 years and usually die of respiratory failure. Although there was no specific cure for the disease until the last 3 years, new treatment modalities, with the improving gene-technology have given good results in progression of the disease and early diagnosis and treatment gained importance.Case: A male 28-days-old baby visited our clinic for routine physical examination and was found to be slightly hypotonic. He had decreased strength in sucking and crying and had slowing in motion in the last 4-5 days. C-reactive protein level was slightly elevated. Since he had a sepsis-like presentation, he was referred to neonatal intensive care unit (ICU). He was given antibiotics and monitored. However, in follow-up he became more hypotonic and deep tendon reflexes were lost. He was diagnosed as SMA type I and was referred for nusinersen (antisense-oligonucleotide) treatment. After treatment, he showed a good progress in motor functions and still does not need any respiratory support.Conclusions: We presented this case to draw attention to SMA in differential diagnosis of hypotonic newborns with sepsis-like presentation and emphasize the importance of early diagnosis and treatment.